Beliefs about Autonomy Support and Control in the Classroom: An Examination of Montessori and Traditional U.S. Public School Teachers - Moss, Jennifer; Wheeler, Theodore (Journal of Montessori Research, 2024)
Montessori education is characterized by autonomous learning, whereas traditional education is often depicted by high structure and fewer choice opportunities. This study examined differences in beliefs of Montessori and traditional teachers in regard to effectiveness, normality, and ease of autonomy-supportive and controlling teaching, as well as differences in motivating styles. We analyzed the U.S. subset from an international study examining self-described motivation styles and beliefs. Our secondary analysis revealed both groups felt autonomy-supportive teaching was easy and effective, and that they found controlling teaching also to be easy, but ineffective. Montessori teachers were more likely to believe autonomy-supportive teaching was normal, whereas traditional teachers believed controlling teaching was more normal. Both groups described their teaching style as autonomy-supportive, but traditional teachers more often rated controlling scenarios as similar to their own practices. These differences, supported by large effect sizes, demonstrate more potential for controlling behavior in traditional classrooms and suggest the possibility of a cultural difference between Montessori and traditional teachers.